2008
DOI: 10.1093/treephys/28.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Tree growth and management in Ugandan agroforestry systems: effects of root pruning on tree growth and crop yield

Abstract: Tree root pruning is a potential tool for managing belowground competition when trees and crops are grown together in agroforestry systems. We investigated the effects of tree root pruning on shoot growth and root distribution of Alnus acuminata (H.B. & K.), Casuarina equisetifolia L., Grevillea robusta A. Cunn. ex R. Br., Maesopsis eminii Engl. and Markhamia lutea (Benth.) K. Schum. and on yield of adjacent crops in sub-humid Uganda. The trees were 3 years old at the commencement of the study, and most specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
6
19
0
Order By: Relevance
“…ring-porous trees with large diameter xylem vessels), removal of branches will directly affect the associated roots, and vice versa (Perry, 1989). Studies of the growth of intercrops in conjunction with Alnus acuminata, Casuarina equisetifolia, Grevillea robusta, Maesopsis eminii and Markhamia lutea indicate that partial pruning of some surface roots may increase the activity of the remaining surface roots, thus providing no overall improvement in crop yield, but have little effect on tree growth (Wajja-Musukwe et al, 2008).…”
Section: Effects Of Tree Management On Root Distribution and Activitymentioning
confidence: 99%
“…ring-porous trees with large diameter xylem vessels), removal of branches will directly affect the associated roots, and vice versa (Perry, 1989). Studies of the growth of intercrops in conjunction with Alnus acuminata, Casuarina equisetifolia, Grevillea robusta, Maesopsis eminii and Markhamia lutea indicate that partial pruning of some surface roots may increase the activity of the remaining surface roots, thus providing no overall improvement in crop yield, but have little effect on tree growth (Wajja-Musukwe et al, 2008).…”
Section: Effects Of Tree Management On Root Distribution and Activitymentioning
confidence: 99%
“…Some reports suggest there is little competition on bench terraces due to spatial or temporal separation of the trees and crops (Cooper et al 1996), although farmers have reported that trees may compete with adjacent crops (Wajja-Musukwe et al 1997;Sun et al 2008). This is important as crop production on the lower terrace is vital for food security during the first 2-3 years after planting while farmers await the benefits of trees grown on the upper terrace.…”
mentioning
confidence: 99%
“…Thus, trees usually compete with crops during the rainy season as their preexisting rooting framework provides a competitive advantage over the emerging roots of germinating crops. Though tree species vary in rooting architecture and root biomass, this is not necessarily reflected by their growth or competitiveness (Wajja-Musukwe et al, 2008). An evaluation of the ratio of root number in the top 1.8 m of soil to trunk volume has shown that Casuarina equisetifolia and Markhamia lutea had significantly higher ratios than A. acuminata, Maesopsis eminii, and Grevillea robusta; Casuarina and Maesopsis were most competitive with crops, whereas Markhamia and Grevillea were least competitive.…”
Section: Why Tree Root Distribution Mattersmentioning
confidence: 99%
“…Pruning offers a direct and adaptable method of controlling competition and has been the focus of several studies in East Africa (Tefera, 2003;Rao et al, 2004;Wajja-Musukwe et al, 2008;Namirembe et al, 2009;Siriri et al, 2010Siriri et al, , 2012. This practice enables farmers to grow the tree species they prefer by managing their growth.…”
Section: Why Tree Root Distribution Mattersmentioning
confidence: 99%